Scientific objectives of research on road machines life cycle in modern conditions - S. A. Evtiukov; S. V. Repin; S. M. Grushetskii; G. A. Kаrro (Вестник СибАДИ, 2020)
Introduction. Many tasks in the field of operation of road machines in modern conditions have become irrelevant from a scientific point of view. This is due to the emergence of new regulatory documents that contribute to the solution of many problems, for example, the tasks of forming fleets of road machines for road maintenance. In addition, the active implementation of CALS-technologies; modern monitoring systems for road machines; the commitment to automate and robotic work processes; change in the volume and pace of road construction; increasing requirements for the quality of work performed; extension of the warranty period of road service; the existence of mega road organizations; the absence to date of generally accepted criteria for evaluating the effectiveness of one form or another of organizing maintenance and repair work (unscheduled repairs) of road machines; active development of a network of toll roads, etc. they require a radical review and systematization of issues related to the formulation of scientific problems in the study of the life cycle system of road vehicles in modern conditions.Materials and methods. The well-known methods of mathematical, factor analysis and expert estimates of parameters were used that determine the main differences that affect mainly on the rational operation of road machines. 218.2.018-2012 ‘Methodological recommendations for determining the necessary fleet of road maintenance equipment for the maintenance of roads in the development of road maintenance projects’ industry road methodology (IRM) contributes to the integrated solution of the main tasks of forming parks with vehicles for road maintenance. Today, the ERA-GLONASS system and similar systems are actively used in all areas of the road economy and allow tracking the position and other technical parameters of road machines over a long period of time. In addition, automation and robotization of production processes are actively used.Results. The factor analysis and the method of expert assessments made it possible to identify the main differences between the modern life cycle system of road machines used for the construction, reconstruction, repair and maintenance of highways than a similar life cycle system of road machines 10-20 years ago. Some features have been identified in the study of the life cycle system of road machines in modern conditions. The main tasks of modern research on the road machines life cycle system are outlined. It has been established that the basis of the industry road guidance documents that have been published at present, as well as those preparing to be published in the nearest future, are largely based on the scientific research conducted 10-20 years ago by Russian scientists. The current industry documents are advisory in modern conditions, which is not always applicable to specific construction objects and sets of road machines, and the installation of tracking systems on road machines only contributes to the scientific research.Discussion and conclusions. In the course of the study, a vector was determined for the further development of such a scientific direction as the study of the life cycle system of the road machines in modern conditions. Some ways are proposed for solving scientific problems, taking into account the modern features of the road machines operations for the construction, reconstruction, repair and maintenance of roads, which allows scientists, especially the young ones, to more accurately and correctly formulate their scientific problems when setting them at the beginning of the research in this area.